UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU MELALUI PENERAPAN PENDEKATAN SUPERVISI KOLABORATIF DI SD NEGERI 44 TARATAK KECAMATAN KOTO XI TARUSAN - Bustam Bustam (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTThe research is motivated by the conditions in the form of: (a) There are quite a number of teachers at SD Negeri 44 Taratak (25%) who have less work motivation, measured by: (1) Teacher's pleasure in doing work, (2) Teacher's work enthusiasm in developing and carry out educational programs or in carrying out learning tasks and other tasks; (3) Alignment of teacher's work towards work standards, (4) Teacher's fighting spirit in achieving educational goals in schools, (5) Consistency of teacher's work when without supervision, and (6) Expression of teacher's happiness when completing assignments and educational commitments at school; (b) The emergence of adverse effects in the form of a lack of success in the goals of education in schools. Tujaun from the implementation of this study is to find out: (1) Steps to implement academic supervision by the principal to teachers to improve teacher work motivation at SD Negeri 44 Taratak, and (2) The magnitude of increasing teacher work motivation after academic supervision is developed by the head school. This research is a school action research which is analyzed with a qualitative approach. The study was conducted at SD Negeri 44 Taratak in the odd semester of the 2017/2018 school year for 5 months. The results of the research are: Implementation of academic supervision in order to improve the work motivation of teachers is done by: (1) Solutions to the problems of teachers in carrying out the learning process and in completing the administration of learning. Problems experienced by teachers are considered as factors that inhibit the emergence of high work motivation so that it must be resolved first; (2) Direct motivation, which is carried out by (a) Showing positive facts that have been achieved by the teacher; (b) Providing Challenges for High Standards of Excellence; (c) Provide expectations for promotion of teacher promotion; (d) Shows the score of the teacher's work achievement; (e) Conveying sanctions that might be applied to the teacher; (f) Presenting school supervisors and heads of local education offices; (g) Creating a friendly atmosphere; (h) Make a joint observation instrument and list of sanctions; (i) Showing the results of observation and open discussion; (j) Giving direct appreciation for the teacher's achievements; (3) The implementation of academic supervision has proven to be able to increase the work motivation of teachers.Kata Kunci : Kompetensi Profesional Guru, Supervisi Kolaboratif